Penggunaan Rehidrasi Cairan Untuk Mencegah Terjadinya Dehidrasi Pada Pasien Anak Dengan Gastroenteritis Akut - Riska Mey Listiana; Murniati M; Suci Khasanah (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Acute gastroenteritis is characterized by watery stools that come up abnormally frequently—three or more times per day—and may contain mucus or blood. One of the consequences is the risk of hypovolemia, which, if not treated immediately, can lead to dehydration. In order to describe the danger of hypovolemia when An. K., who has acute gastroenteritis, is being nursed, this study employs a case study research approach. The case study's main patient, An. K., has nursing concerns and runs the danger of developing hypovolemia when dealing with acute gastroenteritis. Data were gathered through interviews, physical examinations, supporting examinations, documentation, and observation, with a focus on liquid fiber bowel movements >3 times per day and vomiting >4 times per day. Fluid rehydration through fluid monitoring and hypovolemia control are the main nursing interventions. Since the outer requirements, namely fluid intake and urine output, have not yet been satisfied, the 3x24-hour rehydration action has not improved the fluid status. But there has been an increase from the first day of therapy to day three. The best technique to stop dehydration and replace body fluids lost due to diarrhea is obviously nursing, along with rehydration.